The Hellenistic gymnasia of Cyprus and Ptolemaic propaganda - Stavrou, Dorothea (Journal of Greek Archaeology, 2020)
The gymnasion, as is well known, was the centre of the political, social and cultural life of the Hellenistic polis. Its dissemination in the Hellenistic East and its social, cultural and military role have recently become a field of investigation among scholars. The present study aims to cast light on the Cypriot gymnasia and to propose a new approach to them, that of a platform of communication between the authorities and the local population. Through the study of the network of contacts that were constructed in them (among kings, citizens, local elites, members of the royal environment, officials and mercenaries of the royal army), we will examine how the Cypriot gymnasia became bearers of Ptolemaic ideology and to what extent Ptolemaic propaganda was promoted, negotiated, and practised directly and indirectly through them.